Simulation of concrete failure and fiber reinforced polymer fracture in confined columns with different cross sectional shape. (1st March 2017) - Ceccato, Chiara; Salviato, Marco; Pellegrino, Carlo; Cusatis, Gianluca
Highlights: FRP-confined concrete columns are modeled with a meso-scale approach. Concrete failure and fracture of anisotropic material are simulated. Stress vs. strain curves and failure modes are compared to experiments. Abstract: Fiber Reinforced Polymers (FRP) have been widely used in different civil engineering applications to enhance the performance of concrete structures through flexural, shear or compression strengthening. One of the most common and successful use of FRP sheets can be found in the confinement of existing concrete vertical elements which need rehabilitation or increased capacity in terms of strength and ductility. However, efficient design of FRP retrofitting urges the development of computational models capable of accurately capturing (a) the interaction between the axial strains and lateral expansion of concrete with the corresponding stress increase in the external jacket; and (b) the fracturing behavior of the FRP jacket. In this study, experimental data gathered from the literature and relevant to FRP-confined columns are simulated by adopting the Lattice Discrete Particle Model (LDPM) and the Spectral Microplane Model (SMPM), recently developed to simulate concrete failure and fracture of anisotropic materials, respectively. LDPM models the meso-scale interaction of coarse aggregate particles and it has been extensively calibrated and validated with comparison to a large variety to experimental data under both quasi-static and dynamic loading conditions but it has not been fully validated with reference to low confinement compressive stress states, relevant to the targeted application. This task, along with the calibration of SMPM for FRP, is pursued in the present research. The results show that, with the improvement of the existing LDPM constitutive equations to account for low confinement effects, LDPM and SMPM are able to predict the concrete material response governed by the nonlinear interaction of confined vertical members strengthened by means of externally bonded FRP composites.